2017
DOI: 10.7717/peerj.3581
|View full text |Cite
|
Sign up to set email alerts
|

Body and skull morphometric variations between two shovel-headed species of Amphisbaenia (Reptilia: Squamata) with morphofunctional inferences on burrowing

Abstract: BackgroundMorphological descriptions comparing Leposternon microcephalum and L. scutigerum have been made previously. However, these taxa lack a formal quantitative morphological characterization, and comparative studies suggest that morphology and burrowing performance are be related. The excavatory movements of L. microcephalum have been described in detail. However, there is a lack of studies comparing locomotor patterns and/or performance among different amphisbaenids sharing the same skull shape. This pap… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…In the shovel-headed amphisbaenians, specifically L. microcephalum, even small variations in head width may have a major impact on burrowing compression force (Navas et al, 2004) and speed (Hohl et al, 2017). In this case, the analyses of the morphological configuration of the skull presented here indicate that the larger Leposternon specimens or species are able to exert a higher compression force, but dig more slowly, reflecting a trade-off between compression forces and burrowing speeds, as suggested by Hohl et al (2017).…”
Section: Biogeographical Analysismentioning
confidence: 58%
See 2 more Smart Citations
“…In the shovel-headed amphisbaenians, specifically L. microcephalum, even small variations in head width may have a major impact on burrowing compression force (Navas et al, 2004) and speed (Hohl et al, 2017). In this case, the analyses of the morphological configuration of the skull presented here indicate that the larger Leposternon specimens or species are able to exert a higher compression force, but dig more slowly, reflecting a trade-off between compression forces and burrowing speeds, as suggested by Hohl et al (2017).…”
Section: Biogeographical Analysismentioning
confidence: 58%
“…tunnel floor. This cycle ends with the animal dropping its head to return to its initial static position (Barros-Filho, Hohl, & Rocha-Barbosa, 2008;Hohl et al, 2014;Hohl, Loguercio, Sicuro, Barros-Filho, & Rocha-Barbosa, 2017). The shovel-headed morphotype is considered to be the most specialized for digging, which allows these amphisbaenians to penetrate heavily compacted soils (Gans, 1974;Gans, 2005;Hohl et al, 2014;Kearney, 2003).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Early work identified three specialized head shapes, in addition to the more generalized head shape, which are typically associated with different substrates [ 29 ]. More recent work has revealed that changes in skull width can impact burrowing performance between two closely related species [ 30 ] and that skull variation within the genus Leposternon is correlated with biogeographical variables related to soil type [ 31 ]. On the other hand, a study on Caribbean amphisbaenians found no relationship between skull shape and location (a proxy for soil type), and instead found a tight link with phylogenetic history and skull shape [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…The present study describes the food capture behavior of L. microcephalum on the substrate surface in captivity. This species has the shovel-headed morphotype, considered the most specialized for digging (Gans, 1974;Hohl et al, 2017). Gans (1968) suggested that shovel-headed amphisbaenians are less efficient predators than species that share the rounded-headed morphotype.…”
mentioning
confidence: 99%